Botofascism vs Ordinary Fascism – How Martin Karbovski was Stifled by Facebook - Simeonova, Lora (Media and Language, 2019)
The fight against hate speech in the polarized society is becoming more and more fierce. Attempting to overcome it, social networks are commonly trapped into the role of censor of necessity. Governments are also guilty for this phenomenon – trying to regulate big IT companies, authorities are making them vulnerable to manipulations by social engineers and political puppeteers. May the weapons against hate speech become more dangerous than its deeds? Muting one of the most influential voices in Bulgarian media – Martin Karbovski, answers this awkward question.
Keywords: censorship; hate speech; media freedom; manipulations; social networks